The relationship between the development trajectory of symptom burden and exercise adherence during remote pulmonary rehabilitation in olderly patients with COPD - Feng, Li; Ji, Haiyan; Yang, Qing-qing; Liang, Mengyao (Frontiers in Medicine, 2025)
ObjectiveTo investigate the dynamic relationship and interaction between symptom burden and exercise adherence in olderly patients with Chronic obstructive pulmonary disease (COPD) undergoing remote pulmonary rehabilitation, and to establish a foundation for enhancing remote rehabilitation interventions.MethodsA total of 340 olderly patients with COPD, admitted to the Respiratory Center of Nantong Sixth People’s Hospital between May 2023 and February 2025, were selected using a convenience sampling method. The Symptom Burden Scale (SSS-8) and Exercise Adherence Scale were employed to assess symptom burden and exercise adherence levels at baseline (T1), 5 weeks (T2), 9 weeks (T3), and 12 weeks (T4). A cross-lag model was constructed to analyze the causal relationship between these variables.ResultsSymptom burden exhibited a decreasing trend at each stage (F = 36.74, p < 0.001). Exercise compliance demonstrated a gradual increase (F = 38.92, p < 0.001). The cross-lag model indicated that symptom burden and exercise compliance in the early stage (T1-T2) were mutually causal (β = −0.32, p = 0.002; β = −0.24, p = 0.011). Symptom burden in the middle stage (T2-T3) significantly negatively predicted exercise compliance (β = −0.39, p < 0.001). No significant predictive relationship was found between them in the late stage (T3-T4; p > 0.05).ConclusionThe symptom burden of olderly patients with COPD during remote pulmonary rehabilitation is moderate to severe, while exercise compliance is at a moderate level. The dynamic relationship between symptoms and behavior shifts from a bidirectional effect in the early stage to symptom dominance in the middle stage, with no influence in the later stage. It is essential to implement precise interventions tailored to the characteristics of the three-stage trajectory, addressing both symptoms and behavioral obstacles in the early stage, focusing on symptom management in the middle stage, and reinforcing behavioral habits in the later stage.